2017
DOI: 10.1063/1.5001920
|View full text |Cite
|
Sign up to set email alerts
|

Transmission-line resonators for the study of individual two-level tunneling systems

Abstract: Parasitic two-level tunneling systems (TLS) emerge in amorphous dielectrics and constitute a serious nuisance for various microfabricated devices, where they act as a source of noise and decoherence. Here, we demonstrate a new test bed for the study of TLS in various materials which provides access to properties of individual TLS as well as their ensemble response. We terminate a superconducting transmission-line resonator with a capacitor that hosts TLS in its dielectric. By tuning TLS via applied mechanical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…We attribute these fluctuations in Q int to the interaction with an ensemble of charged two-level systems (TLSs), as previously reported in Ref. [37]. At high temperature or high excitation powers, the TLSs are saturated and the observed ripples are smeared.…”
Section: Resultssupporting
confidence: 71%
“…We attribute these fluctuations in Q int to the interaction with an ensemble of charged two-level systems (TLSs), as previously reported in Ref. [37]. At high temperature or high excitation powers, the TLSs are saturated and the observed ripples are smeared.…”
Section: Resultssupporting
confidence: 71%
“…This mechanism is similar to the one proposed to be responsible for qubit dissipation at elevated sample temperatures, where quasiparticles that are tunneling across a JJ can absorb energy from the qubit . The interaction of quasiparticles with single TLS in the tunnel barrier of a phase qubit was studied theoretically by Zanker et al (2016) with experiments performed by Bilmes et al (2017) as described in more detail in Sec. V.…”
Section: B Interactions With Their Dissipative Environmentmentioning
confidence: 99%
“…This technique was used by Lisenfeld et al (2010a) to probe the temperature dependence of TLS energy relaxation and dephasing rates, which at elevated temperatures were found to exceed the rates due to TLS-phonon coupling. The responsible mechanism was identified by Bilmes et al (2017) to originate in the interaction of TLS with BCS quasiparticles, where TLS couple to the evanescent electronic wave function that leaks from the junction electrodes into the tunnel barrier. This work also showed that one may obtain information about the location of TLS across the tunnel barrier by injecting quasiparticles either into the junction's top or bottom electrodes, which can provide clues about the fabrication step in which TLS predominantly emerge.…”
Section: Quantum Dynamics Of Individual Tlsmentioning
confidence: 99%
“…In addition, our setup allows for mechanical TLS tuning by controlling the strain in the sample material with a piezo actuator [14]. Each chip contains 8 slightly different resonators that are coupled to a common transmission line, and is installed in a well-shielded and heavily filtered cryogenic setup that allows for measurements in the single-photon regime at sample temperatures of 30 mK [42]. All capacitors contain a 25-nm thick layer of amorphous AlO x that is deposited in a Plassys system by eBeam-evaporation of aluminum in a low-pressure oxygen atmosphere.…”
Section: Methodsmentioning
confidence: 99%